PEMBUATAN BUSANA BERKUALITAS DARI LIMBAH TEKSTIL MELALUI BRAND CICLO.TH MENGGUNAKAN TEKNIK MIXED MEDIA - Nayoan, Jovinka Rizky; Gema Fitri, An Nisa; Umaroh, Cindi Fadilatul; Maharani, Dewi Astri; Farhan, Farhan; Irianti, Agus Hery Supadmi (Department of Home Economics, Faculty of Engineering, Universitas Negeri Semarang, 2021)
Abstract. In this era of globalization, industrial growth in Indonesia occurs very rapidly, causing environmental problems, especially waste originating from industrial disposal reaching 3% (2018: PKLH). When textile waste ends up in landfills, the clothes will be difficult to decompose. Therefore, it is necessary to minimize overcoming waste pollution. Implementing an upcycle using 3R will minimize the increase in waste due to textiles in Indonesia. The purpose of this paper is to make quality fashion products to reduce textile waste by applying 3R using mixed media techniques. To overcome these problems the method used is the ADDIE Model development method. The development model using ADDIE has 5 stages, namely Analysis (analysis), Design (design), Development (development), Implementation (implementation / execution), and Evaluation (evaluation / feedback). The results of expert validation indicate that this product is feasible to produce, while the results of the implementation by conducting trials in small groups show that this product is up-to-date, cheap, comfortable to use, has a unique motif and has nuances of the culture of the City of Malang. Keywords: waste, used clothes, mixed media, tripshop, and ciclo.th Abstrak. Pada era globalisasi ini pertumbuhan industri di indonesia terjadi sangat pesat, sehingga menimbulkan permasalahan lingkungan, khususnya limbah yang berasal dari pembuangan industri mencapai 3% (2018: PKLH). Ketika limbah tekstil itu berakhir di tempat pembuangan akhir, maka pakaian itu akan sulit terurai. Maka dari itu untuk meminimalisir mengatasi pencemaran limbah dibutuhkan. Menerapkan upcycle menggunakan 3R akan meminimalisir meningkatnya limbah akibat tekstil di Indonesia. Tujuan dari penulisan ini adalah Membuat Produk busana berkualitas guna mengurangi limbah tekstil dengan menerapkan 3R dengan menggunakan teknik mixed media. Untuk mengatasi permasalahan tersebut metode yang digunakan adalah metode pengembangan Model ADDIE. Model pengembangan menggunakan ADDIE terdapat 5 tahap yaitu Analysis (analisa), Design (desain/perancangan), Development (pengembangan), Implementation (implementasi/eksekusi), dan Evaluation (evaluasi/ umpan balik). Hasil validasi ahli menunjukkan produk ini layak diproduksi, sedangkan hasil implementasi dg melakukan uji coba pada kelompok kecil menunjukkan bahwa produk ini Uptodate, murah, nyaman dipakai, motifnya unik serta bernuansa budaya Kota Malang. Kata Kunci: limbah, pakaian bekas, mixed media, triftshop, dan ciclo.th